Ion channels and tranporters in cancer. 2. Ion channels and the control of cancer cell migration - Cuddapah, Vishnu Anand (American Physiological Society, 2011)
A hallmark of high-grade cancers is the ability of malignant cells to invade unaffected tissue and spread disease. This is particularly apparent in gliomas, the most common and lethal type of primary brain cancer affecting adults. Migrating cells encounter restricted spaces and appear able to adjust their shape to accommodate to narrow extracellular spaces. A growing body of work suggests that cell migration/invasion is facilitated by ion channels and transporters. The emerging concept is that K(+) and Cl(−) function as osmotically active ions, which cross the plasma membrane in concert with obligated water thereby adjusting a cell's shape and volume. In glioma cells Na(+)-K(+)-Cl(−) cotransporters (NKCC1) actively accumulate K(+) and Cl(−), establishing a gradient for KCl efflux. Ca(2+)-activated K(+) channels and voltage-gated Cl(−) channels are largely responsible for effluxing KCl promoting hydrodynamic volume changes. In other cancers, different K(+) or even Na(+) channels may function in concert with a variety of Cl(−) channels to support similar volume changes. Channels involved in migration are frequently regulated by Ca(2+) signaling, most likely coupling extracellular stimuli to cell migration. Importantly, the inhibition of ion channels and transporters appears to be clinically relevant for the treatment of cancer. Recent preclinical data indicates that inhibition of NKCC1 with an FDA-approved drug decreases neoplastic migration. Additionally, ongoing clinical trials demonstrate that an inhibitor of chloride channels may be a therapy for the treatment of gliomas. Data reviewed here strongly indicate that ion channels are a promising target for the development of novel therapeutics to combat cancer.